ANALISIS MUATAN KEKERASAN PADA FILM ANIMASI â€œOSCAR OASISâ€ BERDASARKAN PRINSIP EXAGGERATION - Wiraatmaja, Angga (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2018)
Many children like watching animation and gain knowledge from it. However, many animations contain violence in their scenes. Therefore, parents need to be aware that the scenes potentially give negative impact on children attitude and behaviour. This research focuses on the analysis of positive and negative side of â€œOscar Oasisâ€ animation movie based on exaggeration principle. Quantitative content analysis is employed as the method. The result shows several types of violence in the movie such as beating, persecution, raiding, slaughtering, rough / sharp throwing, kicking, and fights. The duration of the violence is also counted.